Pengembangan bahan ajar tajwid dengan flipbook di Madrasah Tsanawiyah - Addimasyqi, Moh. Ridham; Tamam, Abas Mansur; Alim, Akhmad (Tawazun: Jurnal Pendidikan Islam, 2024)
The purpose of this study is to analyze the need for the development of tajweed teaching materials with flipbooks in MTs, make tajweed teaching materials with flipbooks in MTs, determine the feasibility of tajweed teaching materials with flipbooks in MTs and find out the level of effectiveness of tajweed teaching materials with flipbooks in MTs. The results of this study show that the majority of 97% in MTs Utsmanil Hakim and 96% agree on the need for the development of electronic-based tajweed teaching materials. The tajweed material presented in this teaching material is the science of tajweed, makhraj and the nature of letters, tarqiq and tafkhim, the law of nun sukun and tanwin, the law of mim sukun, the law of mad thabi’i and far’i, waqaf and ibtida’, gharib readings developed with the Canva and Heyzine applications. The feasibility of tajweed teaching materials with flipbooks at Madrasah Tsanawiyah is validated by material, media, and language experts. Validation from media experts obtained a score of 82% classified as "Very Feasible", validation by media experts obtained a score of 95% classified as "Very Feasible", validation by linguists obtained a score of 96.25% in the "Very Feasible" category.The tajweed teaching materials were tested in two schools, the first at MTs Utmanil Hakim with experimental class VII A had an average pretest score of 63 and the pretest in experimental class VII A experienced a significant increase in the average posttest score to 89. The N-Gain score obtained by the VII A experimental class was 0.712 and the level of effectiveness of using tajweed teaching materials with flipbooks was high. Abstrak Penelitian ini bertujuan adalah menganalisis kebutuhan pengembangan bahan ajar tajwid dengan flipbook di MTs, membuat bahan ajar tajwid dengan flipbook di Madrasah Tsanawiyah, mengetahui kelayakan bahan ajar tajwid dengan flipbook di MTs dan mengetahui tingkat efektivitas bahan ajar tajwid dengan flipbook di MTs. Metode yang digunakan dalam penelitian ini adalah R&D dengan model ADDIE. Hasil penelitian ini menunjukkan bahwa, mayoritas 97% di MTs Utsmanil Hakim dan 96% setuju perlu adanya pengembangan bahan ajar tajwid berbasis elektronik. Materi tajwid yang disajikan dalam bahan ajar ini adalah ilmu tajwid, makhraj dan sifat huruf, tarqiq dan tafkhim, hukum nun sukun dan tanwin, hukum mim sukun, hukum mad thabi’i dan far’i, waqaf dan ibtida’, bacaan gharib yang dikembangkan dengan aplikasi Canva dan Heyzine. Kelayakan bahan ajar tajwid dengan flipbook di Madrasah Tsanawiyah di validasi oleh ahli materi, media, dan bahasa. Validasi dari ahli media didapatkan nilai 82% tergolong “Sangat Layak”, validasi ahli media didapatkan nilai 95% tergolong “Sangat Layak”, validasi ahli bahasa didapatkan nilai 96,25% kategori “Sangat Layak”. Bahan ajar tajwid diuji coba dalam dua sekolah, pertama di MTs Utmanil Hakim dengan kelas eksperimen VII A memiliki nilai rata-rata pre-test sebesar 63 dan pre-test di kelas eksperimen VII A mengalami peningkatan signifikan dalam nilai rata-rata post-test menjadi 89. Hasil skor N-Gain yang diperoleh kelas eksperimen VII A adalah sebesar 0,712 dan tingkat efektivitas penggunaan bahan ajar tajwid dengan flipbook termasuk tinggi.